2022
DOI: 10.35631/ijepc.745017
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Difficulties and Self-Criticism Among University Students During Covid 19 Pandemic in Indonesia

Abstract: This study examined the relationship between emotion regulation difficulties and self-criticism among college students during the COVID-19 pandemic. The study explores how particular aspects of emotion regulation difficulties correlate to the self-criticism dimension. Participants were 1049 college students from a university in the capital city (84 % female and 16% male). Students came from eight faculties (faculty of education, art and language, social science, technics, sport science, educational psychology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Following our discussion above, this is not surprising. Interestingly, we found that even medium levels of experience with technology can contribute to sense of success and self-efficacy when facing emotional difficulties, which highlights the importance of such experience; although technology use in teaching is often accompanied by anxiety among teachers (Al-Fudail & Mellar, 2008;Fernández-Batanero et al, 2021), acceptance of technology during COVID-19 days was found to be positively associated with positive mental health, which may explain this findings (Wahyuni et al, 2021).…”
Section: Prominence Of Experience Of Teaching With Technology and The...mentioning
confidence: 62%
“…Following our discussion above, this is not surprising. Interestingly, we found that even medium levels of experience with technology can contribute to sense of success and self-efficacy when facing emotional difficulties, which highlights the importance of such experience; although technology use in teaching is often accompanied by anxiety among teachers (Al-Fudail & Mellar, 2008;Fernández-Batanero et al, 2021), acceptance of technology during COVID-19 days was found to be positively associated with positive mental health, which may explain this findings (Wahyuni et al, 2021).…”
Section: Prominence Of Experience Of Teaching With Technology and The...mentioning
confidence: 62%
“…Furthermore, it would be crucial to address research regarding the link between SC and psychopathology and extending this investigation to the potential connections with adverse conditions. For instance, a study conducted by Wahyuni et al., ( 108 ) in the university population documented the impact of adverse events (i.e., the COVID-19 pandemic) on SC levels, a finding replicated among healthcare professionals exposed to potentially morally injurious events during the pandemic ( 109 ). This is an important challenge from an epistemological point of view that might contribute to more effective plans and tailored interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Sistem perlindungan diri ini jika diaktifkan terusmenerus akan menimbulkan stres (Gilbert, 2009b). Ketika mahasiswa gagal memperoleh umpan balik positif dari teman sebaya, orang tua, dan dosen, mahasiswa cenderung merangsang sistem untuk kritis terhadap diri sendiri dan melakukan kritik diri (Wahyuni et al, 2021).…”
Section: Kritik Diriunclassified